Investigating the Effects of Social Determinants of Traffic Crash Mortality in Isfahan City - Hasan Jafari; Mostafa Amini-Rarani; Mohammad Ranjbar; Milad Shafiee; Ashraf Haj-Hashemi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Introduction Many people die as a result of road traffic crashes globally every year. Low- and middle-income countries had higher road crashes mortality compared to high-income countries and Iran is one of the countries with the high road crashes mortality in the world. Regarding the important and basic role the social components plays in health. The current study aims to investigate social determinants of traffic crash mortality in Isfahan during the 2014-2017. Methods: This study was a cross-sectional data secondary analysis. 29909 traffic crashes were analyzed. Data were extracted from the Hospital Information System (HIS) and analyzed using logistic regression. Social determinants were selected using the Commission on Social Determinants of Health conceptual framework. Data were analyzed with Stata 14 software at a significance level of less than 0.05 Results: we found that 719(2.8%) mortalities were related to traffic accident injury. The death rate due to traffic crash in the hospital was 2.4%. Multivariate logistic regression showed that men (P-value =0.00), unemployed people, less than 65 years of age, injured transported from suburb and passengers of small vans/trucks (P-value <0.00) had higher odds of mortality caused by traffic crashes Conclusions: Considering the importance of social factors on traffic crashes mortality, health policy-makers should develop preventive programs and adopting policies based on occupation, sex, age, mode of transport of the injured, and the type of vehicles to inform interventions aimed at reducing injury-related mortality.